2012
DOI: 10.1128/aac.00066-12
|View full text |Cite
|
Sign up to set email alerts
|

The Aminoglycoside Antibiotic Kanamycin Damages DNA Bases in Escherichia coli: Caffeine Potentiates the DNA-Damaging Effects of Kanamycin while Suppressing Cell Killing by Ciprofloxacin in Escherichia coli and Bacillus anthracis

Abstract: The distribution of mutants in the Keio collection of Escherichia coli gene knockout mutants that display increased sensitivity to the aminoglycosides kanamycin and neomycin indicates that damaged bases resulting from antibiotic action can lead to cell death. Strains lacking one of a number of glycosylases (e.g., AlkA, YzaB, Ogt, KsgA) or other specific repair proteins (AlkB, PhrB, SmbC) are more sensitive to these antibiotics. Mutants lacking AlkB display the strongest sensitivity among the glycosylase-or dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 71 publications
7
46
0
Order By: Relevance
“…a significant role in the lethality of bactericidal antibiotics. These results, along with recent observations that kanamycin can damage DNA bases (26) and induce SOS response in strains with mutated 8-oxo-dG-processing genes (mutM, mutY, and mutT) (96), highlight a DNA-damaging component to aminoglycoside lethality, as is consistent with previous MutT results (25). More broadly, these findings suggest that suppressive alterations to proton motor force cannot wholly explain anaerobic protection against aminoglycoside lethality (49)(50)(51).…”
Section: Fig 5 Ros Contribute To the Lethality Elicited By Bactericsupporting
confidence: 78%
“…a significant role in the lethality of bactericidal antibiotics. These results, along with recent observations that kanamycin can damage DNA bases (26) and induce SOS response in strains with mutated 8-oxo-dG-processing genes (mutM, mutY, and mutT) (96), highlight a DNA-damaging component to aminoglycoside lethality, as is consistent with previous MutT results (25). More broadly, these findings suggest that suppressive alterations to proton motor force cannot wholly explain anaerobic protection against aminoglycoside lethality (49)(50)(51).…”
Section: Fig 5 Ros Contribute To the Lethality Elicited By Bactericsupporting
confidence: 78%
“…Caffeine has previously been shown to exhibit antibacterial activity against E. coli through interfering with DNA synthesis (108,109). It prevented the removal of thymidine dimers induced by UV radiation, contributing to increased mutational frequency (110).…”
Section: Figmentioning
confidence: 99%
“…reported that E. coli cells deficient for alkB , a DNA repair gene, are much more sensitive to the aminoglycoside kanamycin compared to wild type cells [42], suggesting a potential role for DNA damage in cell killing by aminoglycosides. Since alkB is a part of the adaptive response to alkylation [43, 44], prior exposure to very low-levels of alkylating agents induces the expression of alkB as well as other member genes of the adaptive response regulon [45].…”
Section: Resultsmentioning
confidence: 99%
“…Exocyclic DNA adducts such as ethenoadenine are known to be induced by products of lipid peroxidation [46], leading Kang et al . to speculate that aminoglycosides promote membrane lipid peroxidation resulting in the formation of exocyclic adducts targeted by AlkB [42]. However, it should be noted that the range of target lesions repaired by AlkB includes the potent replication-blocking methylated bases 1-methyladenine and 3-methylcytosine, which are formed when endogenous (or exogenous) alkylating agents attack single-stranded DNA [4749].…”
Section: Resultsmentioning
confidence: 99%